Herbivore effect traits and their impact on plant community biomass: an experimental test using grasshoppers - Luca Borger (Functional Ecology, 2014)
1. Using trait-based approaches to study trophic interactions may represent one of the most promising approaches to evaluate the impact of trophic interactions on ecosystem functioning. To achieve this goal, it is necessary to clearly identify which traits determine the impact of one trophic level on another.2. Using functionally contrasting grasshopper species, we tested the ability of multiple traits (morphological, chemical and biomechanical) to predict herbivore impact on the biomass of a diverse plant community. We set up a cage experiment in an old species rich grassland field and evaluated how multiple candidate grasshopper effect traits mediated herbivore impact on plant biomass.3. Grasshoppers had different impact on plant community biomass (consuming up to 60 % of plant community biomass). Grasshopper impact was positively correlated with their incisive strength while body size or grasshopper C:N ratio exhibited low predictive ability. Importantly, the strong relationship between the incisive strength and the impact was mediated by the grasshopper feeding niche, which was well predicted in our study by two simple plant traits (leaf dry matter content, leaf C:N ratio). Feeding niche differences between grasshoppers were explained by differences in incisive strength, highlighting the fundamental linkage between grasshopper effect traits and their niche.4. Our study contributes to the development of the trait-based approach in the study of trophic interactions by providing a first experimental test of the relationship between herbivore effect traits, their impact on plant community biomass, and in a larger extent on ecosystem functioning. By comparing the relative importance of multiple interacting grasshopper traits, our study showed that incisive strength was a key effect trait which determined grasshopper feeding niche and its relative impact on plant community biomass.